Base nacional comum curricular e o processo de construção do documento orientador curricular de Santa Maria/RS: da prescrição à indução de políticas educacionais - Mattos, Kélli Renata Corrêa de (2021)
For decades, discussions about a common curriculum have been the focus of Brazilian public policy. The implementation of the Common National Curricular Base (BNCC) configures a process of homogenization of education and has been taking shape not only nationally but also at state and municipal levels. The study in question aims to analyze how the process of construction of the Documento Orientador Curricular de Santa Maria (DOC/SM) occurred. The research is characterized as qualitative, with document analysis, literature review and field study. The data production occurred through participant observation of the construction of the DOC/SM and semi-structured interviews with two teachers and a manager of the area of Nature Sciences, both participants of the Articulation and Systematization Commission of the document. The analysis of this study was conducted from the Policy Cycle proposed by Stephen Ball and collaborators, from macro context (Public Policy - BNCC) to microcontext (municipal document - DOC/SM). Two contexts of the Policy Cycle were analyzed: context of influence and context of text production. The context of influence, demonstrates how the process of globalization, internationalization and neoliberalism, act in the homogenization and commodification of the curriculum. It identifies the power relations and the significant intervention of international organizations in public policies of education, especially those of curricular impact. The context of the production reveals the turbulent process of construction of the BNCC, its versions and the opposition of national education associations / teaching and societies representing the area of Nature Sciences. It also addresses the process of construction of the DOC/SM, from the perspective of the participating researcher, the teachers and the manager of the area of Natural Sciences. With this study, we can understand how Brazilian educational public policies are aligned with global standards, economic and political interests. In the selection of certain knowledge in detriment of others, the curriculum reveals itself as a fertile ground for persuasion and control, thus being the scope of dominant groups. This intent of interfering with different entities for the insertion of economic, political and ideological issues, can be observed from the national curriculum-BNCC to the weaving of the municipal document itself-Santa Maria-DOC/SM.